Difficulties Faced by Early Childhood Teachers in Learning Science in Early Childhood - Putri Sari Ulfa Sembiring; Muhammad Dekar Nasution (Outline Journal of Education, 2024)
Early childhood education (PAUD) as the basis for children's higher education and preparing a generation of learners who have a healthy competitive spirit is very important. This can be done through science learning. This research analyzes the difficulties of PAUD teachers in teaching science to early childhood. The method used was qualitative descriptive with a sample of 20 PAUD teachers in Mangga Village, Medan Tuntungan District, Medan City. The data obtained was analyzed using the informant review technique or feedback from informants by Milles and Hubberman. To ensure the validity of the data collected, triangulation techniques were also used. The results of the research show that PAUD teachers have difficulties in teaching science, understanding science concepts which are still rigid by following reference books, limited tools, materials and time, as well as applying science concepts which do not yet refer to the early childhood environment. Based on the results of this research, it can be concluded that the competence of PAUD teachers must be improved in accordance with the aim of teaching science to early childhood.